The Influence of Corporate Philanthropy and Risk Management on Corporate Value - Suwarno, Suwarno; Mujanah, Siti; Halik, Abdul (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2024)
Corporate sustainability has become a critical concern for stakeholders, emphasizing that management's focus should extend beyond short-term profit maximization to encompass the broader welfare of all stakeholders. Through the adoption of strategic philanthropic initiatives and the implementation of robust risk management practices, companies can address stakeholder expectations while strengthening their competitive position in dynamic market environments. This study aims to analyze the influence of corporate philanthropy and risk management on firm value. Utilizing a sample of 112 manufacturing companies listed on the Indonesia Stock Exchange for the 2022 period, this research employs regression analysis, preceded by classical assumption tests to ensure the validity and reliability of the data. The findings reveal that both corporate philanthropy and risk management have a significant positive effect on firm value, underscoring the importance of socially responsible practices and effective risk mitigation in fostering sustainable corporate growth and long-term stakeholder trust.